THE ANALYSIS ON CANONICAL CORRELATION OF GLOBAL INDEX AND MACRO ECONOMY WITH INDONESIAN CAPITAL MARKET - Amir, Afriza; Sadalia, Isfenti; Fachruddin, Khaira Amalia (JEBIM Prima, 2020)
Capital market is one of the media which gives the opportunity for individual and insttutional investors to invest. The Indonesia Stock Exchange and Indonesian capital market has 11 types of stock priced index which as continously spread through printed and electronic mass media, as one of the guidelines for investor to invest in capital market. The development of indonesian capital market (LQ45 Index and IHSG Index) is closely related to global index and macro economy. The objective of the reseach was to examine the canonical correlation of global index (Dow Jones Index and EIDO Index) and macro economy (Rupiah Exchange Rate and SBI interest rate) with indonesian capital market (LQ45 Index and IHSG Index). The sample were limited to the period of 2011-2013 (36 months).The data were analyzed by using canonical correlation at the significant level of 5%. The result of the research showed that global index (Dow Jones Index and E10) and macro economy (rupiah exchange rate and SBI interest rate) had significant correlation with indonesian capital market (LQ45 and IHSG), with canonical coefficients perfect weight for L045 (1.00) and almost perfect for JCI (0.98). This means that the Dow Jones. EIDO exchange rate, interest rate SBI has a significant positive relationship towards LQ45 Index and IHSG Index are listed on the Indonesia Stock Exchange in the period 2011 to 2013 Individually Dow Jones (0.67), EIDO (0.54) and Exchange Rate (0.37) has a positive relationship with the capital market indices Indonesia (L045 Index and IHSG Index), which means when the Dow Jones. EIDO, and Rupiah Exchange high, then LQ45 and IHSG will be high, or vice versa when the Dow Jones, EIDO, and Exchange Rate is low, then the Index will be lower LQ45 and IHSG. Instead SBI rate (-0.29) had a negative correlation with stock market indices Indonesia (LQ45 Index and IHSG Index), which means if the SBI interest rate is high, then LQ45 and IHSG will be low, or vice versa when the Indonesian interest rate is low, then LQ45 and IHSG will be high